THE ROLE OF CHESS AND LOGIC GAMES IN DEVELOPING PERSONAL THINKING - Bobokulov Chori Urolovich (Journal Park Publishing, 2025)
This article discusses the role of chess and logic games in the development of personal thinking and their educational and educational potential. Chess and various logic games serve to activate students' thinking, form critical and creative thinking, develop the ability to analyze problems and find optimal solutions. During the study, the pedagogical and psychological aspects of using chess and logic games were studied, their advantages in strengthening personal thinking were analyzed. Also, the methodology for using these games at the primary and secondary education levels and their role in increasing the intellectual potential of students were substantiated. The results obtained show that chess and logic games are an effective tool not only for consolidating knowledge, but also for developing the culture of personal thinking of students.
Keywords: Personal opinion, chess, logical games, critical thinking, creative thinking, intellectual development, educational process, pedagogical opportunities, problem solving, strategic thinking.